Effect of Continuous Use of Manures and Fertilizers on the Chemistry of Phosphate in Meadow-Chernozemic Soils of U.S.S.R - Chandra, S.K.; Lisoval, A.P. (Asian Journal of Chemistry, 2010)
Long term application of organic manures and inorganic fertilizers in meadow-chernozemic soils of Kiev (U.S.S.R.) increased, total organic, inorganic and available P status of soils. 43–52% of total P was in organic form. Positive correlation (r═0.927) was found between total P and organic P. Phospholipids and nucleic acids content of these soils were markedly increased by application of manures and fertilizers. The inositol phosphates content of meadow-chernozemic soils remained unaffected under long term fertilisation.